Specific Blocking to Improve Biopanning in Biological Samples such as Serum and Hybridoma Supernatants - Bradley T. Messmer; David S. Thaler (BioTechniques)
Screening phage-displayed peptide libraries (biopanning) is an important technique for acquiring peptide ligands and for mapping peptide epitopes recognized by antibodies (Ab). In biological samples, other materials, not only contaminants but also natural constituents, often interfere with biopanning. Capture methods use anchoring Abs that reduce the need for purification of the intended panning target from a crude sample. This capture method is analogous to sandwich ELISA. However, when the target molecule concentration is low in the initial mixture, the panning of a captured target often yields epitopes that bind to the capture antibody rather than the target of interest. We have developed a methodology that utilizes specific blocking reagents of the capture Ab to extend the sensitivity and applicability of the capture approach to phage panning. A flowchart is presented to enable the worker to begin panning with the simplest approach and then to employ sandwich capture and specific blocking reagents as necessary.